Synergy of Government, Community, and Private Sector Regarding Effective Collaboration in Regional Governance - Nahruddin, Zulfan; Handam, Handam (Generasi Sains Indonesia, 2024)
This article is focused on how the government works with community and private players in enhancing good regional governance. Due to challenges like urbanization, environment, and even economic disparity, such other regional sectors can only enable development and enhance welfare through collaboration. The review also sketches out factors such as vision, appraisal of roles and responsibilities, trust and transparency that help to foster a successful collaboration. It also captures factors including conflicts of interest and objective, resource constraints, and policy and institutional constraints which facilitate the breakdown of the collaboration. Based on examples of countries and cities from across the globe, the review looks at practices that have proven the usefulness of cooperation, including Surabaya’s Green and Clean Program, the transformation of Medellin and the integration of the sound Region to show that partnerships with the ability to coordinate across different business sectors are capable of producing positive outcomes. Besides, it shows success stories and models of collaboration and highlights what promotes effective actions: involvement, commitment over time, and adaptability. Therefore, in line with the research objective, the review finds that effective coproduction initiatives are more likely to be socially sustainable when the collaborative relationships are strategic, based on mutual trust and shared vision.